2, 2′-Bipyridine and hydrazide containing peptides for cyclization and complex quaternary structural control. (23rd April 2018) - Hernandez, Erik T.; Escamilla, P. Rogelio; Kwon, Sang-Yop; Partridge, Jonathan; McVeigh, Matthew; Rivera, Sebastian; Reuther, James F.; Anslyn, Eric V.
Abstract : Complex quaternary structure formation of bipy peptide ligands. Abstract : A synthetic peptide containing two N ε -methyl lysines (Ac-K( N ε -Me)GYTGYTGK( N ε -Me)D-OH) was alkylated with bipyridine (bipy) ligands substituted at the fifth (MP-5 ) and sixth (MP-6 ) positions, thereby creating Ac-K( N ε -Me, N ε -Bipy)GYTGYTGK( N ε -Me, N ε -Bipy)D-OH. Peptides with a bipyridine at the 6-position did not bind to Fe 2+ and Zn 2+ . Peptides with a bipyridine at the 5-position bound these metals, and in the presence of one equivalent of a free bipy derivative folded into a macrocycle. Further, the free bipy derivative could also contain a cyclized peptide derived from hydrazone formation, resulting in a complex but controlled quaternary peptide structure.